2023
DOI: 10.1002/stvr.1840
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty quantification for deep neural networks: An empirical comparison and usage guidelines

Abstract: SummaryDeep neural networks (DNN) are increasingly used as components of larger software systems that need to process complex data, such as images, written texts, audio/video signals. DNN predictions cannot be assumed to be always correct for several reasons, amongst which the huge input space that is dealt with, the ambiguity of some inputs data, as well as the intrinsic properties of learning algorithms, which can provide only statistical warranties. Hence, developers have to cope with some residual error pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(100 reference statements)
0
0
0
Order By: Relevance
“…Uncertainty estimation forms a significant component of software testing for software containing deep learning elements. Previous research has found various techniques from uncertainty estimation effective in reducing defects and vulnerabilities of software containing deep neural networks [52], [65]. The main methodology for employing uncertainty quantification techniques for reducing defects in software containing deep neural networks is to use a supervisor module in a deep neural network software system that evaluates whether a given prediction by the deep neural network should be trusted or not.…”
Section: Uncertainty Quantificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Uncertainty estimation forms a significant component of software testing for software containing deep learning elements. Previous research has found various techniques from uncertainty estimation effective in reducing defects and vulnerabilities of software containing deep neural networks [52], [65]. The main methodology for employing uncertainty quantification techniques for reducing defects in software containing deep neural networks is to use a supervisor module in a deep neural network software system that evaluates whether a given prediction by the deep neural network should be trusted or not.…”
Section: Uncertainty Quantificationmentioning
confidence: 99%
“…The main methodology for employing uncertainty quantification techniques for reducing defects in software containing deep neural networks is to use a supervisor module in a deep neural network software system that evaluates whether a given prediction by the deep neural network should be trusted or not. Recent empirical work has found measures developed for uncertainty quantification to work well for the supervisor module [65]. As such, these uncertainty estimation techniques have been thoroughly empirically validated for their use in software engineering [65], and a Python package is even available for developers to implement many of these uncertainty quantification techniques as part of their software development [53].…”
Section: Uncertainty Quantificationmentioning
confidence: 99%
See 1 more Smart Citation